STRATEGI PENINGKATAN PEMBELAJARAN UPACARA ADAT PENGANTIN SIRAMAN DENGAN MENGGUNAKAN SIMULASI PADA MAHASISWA TATA RIAS AKS-AKK YOGYAKARTA - Yuwati, Herina; Warsihapsari, Tri (Jurnal Socia Akademika, 2024)
This study aims to 1) find out how far students are interested in the traditional wedding ceremony course, 2) find out the learning outcomes of students using the simulation method. The research method used is quantitative descriptive. The subjects in this study are 42 people from semesters IV and VI of the AKS AKK Yogyakarta Cosmetology Study Program. Data collection uses documentation, interviews and observations. The results of the study stated that the simulation method was 100% interesting in learning the traditional ceremony of the bride and groom. Students become more understanding, more understanding, and more active in the learning because they pretend to play the role of actors in the bridal shower ceremony. So that this makes it easier for lecturers to convey messages in the teaching and learning process and students understand it more easily